Students seek gifts for Boys and Girls Club of El Dorado Park - Uribes, Tom::::::::: (2013)
Associated Students, Inc. keeps up its drive to spread holiday cheer by giving out gifts to the teens residing in the El Dorado Park neighborhoods west of Bulldog Stadium.